A study into rights of refugee in Malaysia / Adi Syafiq Osman and Lukman Hakim Abu Bakar - Osman, Adi Syafiq; Abu Bakar, Lukman Hakim (2007)
For the last two semesters we have bee conducting a research on the rights in Malaysia and the world, in 21st century, as globalization is faced by major country, the problem of refugee become more serious. They must be recognized as human and they deserved the right to live. In humanitarian basis we must ratified the refugee status and provided them with basic protection and facility. Although this right is laid down in the international convention and treaties and as far as concern, our country did not ratified this convention and treaties, due to this situation we did not recognized the status of refugees. This research is based on Convention relating to the Status of refugee 1951 and 1967 protocol. This convention provided the protection and recognized the refugee right. This research also deal with historical and development of this convention. The aim of this research is to determine and interpreted the rights of refugee by the ratification of 1951 convention. Hopefully, this research will benefit the society and our country to recognized refugee and admit their rights.